2013
DOI: 10.2166/wst.2013.335
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the die-off of E. coli and Ascaris in wastewater-irrigated vegetables: implications for microbial health risk reduction associated with irrigation cessation

Abstract: This study assessed the die-off of Escherichia coli (E. coli) and Ascaris suum on lettuce (Great Lakes 118) and cabbage (Brassica oleracea var capitata) in wastewater-irrigated fields using comparative mathematical die-off models. The study revealed that none of the survival curves of E. coli and A. suum was best fitted with the log-linear model, indicating that the classical first-order kinetic approach is inadequate in many cases. The biphasic die-off model best described the die-off of E. coli on lettuce (k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…All enteric pathogens of viral, bacterial and parasitic (helminthic and protozoan) origins can be found in wastewater; and can be transmitted to farmers using the wastewater for irrigation, consumers of wastewater-irrigated vegetables and communities close to wastewater irrigated fields [5]. Several studies have shown a significant relationship between Ascaris infection and exposure to wastewater (either treated or untreated) [6,7,8]. This is because soil transmitted helminths (STHs) (such as Ascaris ) can survive for long periods of time under severe adverse environmental conditions [9] contributing to their high risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…All enteric pathogens of viral, bacterial and parasitic (helminthic and protozoan) origins can be found in wastewater; and can be transmitted to farmers using the wastewater for irrigation, consumers of wastewater-irrigated vegetables and communities close to wastewater irrigated fields [5]. Several studies have shown a significant relationship between Ascaris infection and exposure to wastewater (either treated or untreated) [6,7,8]. This is because soil transmitted helminths (STHs) (such as Ascaris ) can survive for long periods of time under severe adverse environmental conditions [9] contributing to their high risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, simple first‐order (single‐phase) die‐off is probably not accurate as most soil and subsurface environments are highly heterogeneous and because of the potential for long‐term survival of persistent subpopulations and/or re‐growth in the environment (Bradford and others ). As such, biphasic survival kinetics have been observed in both water (Easton and others ; Ahmed and others ) and fresh produce production environment (Petterson and others ; Seidu and others ). In biphasic decay kinetics an initial rapid decay is noted, often followed by an attenuated, slower decay.…”
Section: Resultsmentioning
confidence: 96%
“… Diallo and others () Seidu and others () Barker and others (); Ottoson and others () Bastos and others (); Domenech and others (); Mara and others (); Rodriguez and others (); Or Oron and others (); Van Ginneken and Oron () …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration and temperature conditions of storage between purchase and consumption can play a role in potential survival, decline, or growth of certain pathogens on fresh-cut produce and will influence the outcome of microbiological risk assessments (7,17,45) for leafy greens in various distribution chains. The behavior of pathogens on fresh produce has been investigated using laboratory experiments and modelling (e.g., Escherichia coli 0157:H 7, Salmonella, and Listeria monocytogenes on leafy greens (23,32) and fresh-cut iceberg lettuce (28)) and real-life experiments (42,48).…”
Section: Consumption Data Expressed As Acute Intakementioning
confidence: 99%